2017
DOI: 10.1002/lary.26567
|View full text |Cite
|
Sign up to set email alerts
|

Increased long‐term risk of hearing loss in patients with traumatic brain injury: A nationwide population‐based study

Abstract: 2b. Laryngoscope, 127:2627-2635, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…Unfortunately, many of these studies incorporated a range of TBI categories from mild to severe and may have included patients with temporal bone fractures. TBI can occur in mild, moderate, and severe forms, and nonspecific inclusion of patients with all types of TBI without discussion of temporal bone fracture makes interpretation and generalization of these studies challenging …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many of these studies incorporated a range of TBI categories from mild to severe and may have included patients with temporal bone fractures. TBI can occur in mild, moderate, and severe forms, and nonspecific inclusion of patients with all types of TBI without discussion of temporal bone fracture makes interpretation and generalization of these studies challenging …”
Section: Discussionmentioning
confidence: 99%
“…TBI can occur in mild, moderate, and severe forms, and nonspecific inclusion of patients with all types of TBI without discussion of temporal bone fracture makes interpretation and generalization of these studies challenging. 14,[41][42][43] Beyond the civilian literature, research has been completed in military personnel who sustained blast-related TBI and/or acoustic trauma. Hearing loss and tinnitus are the two most prevalent service-connected conditions in this sample population.…”
Section: Fig 4 (A) Percentage Of Mtbi Versus Controls Patients Withmentioning
confidence: 99%
“…Schuknecht's above-mentioned study with cats confirmed the most common hearing loss to occur was a sensorineural hearing loss with notching at 3–8 kHz—quite similar to what is seen with occupational noise-induced hearing loss. A recent review of the Taiwan National Health Insurance Database of 553,286 TBI patients, compared to 1.1 million patients without TBI, demonstrated a 2.125x increased risk of hearing loss among the TBI patients ( 8 ). The most common source of trauma was a motor vehicle accident.…”
Section: Testingmentioning
confidence: 99%
“…The National Health Research Institute (NHRI) of Taiwan has maintained a large computerized administrative database assembled from the National Health Insurance (NHI) medical records, including data on outpatient visits, hospital admissions, prescriptions, and disease status for all insurant. The NHI program covers 99.9% of the 23.74 million people residing in Taiwan [ 5 , 6 ]. The NHRI encrypts patients’ personal information for privacy protection and provides researchers with anonymous identification numbers associated with relevant claim information, including patient sex, date of birth, registry of medical services, and medication prescriptions.…”
Section: Methodsmentioning
confidence: 99%